Patterns of Child Grooming and Sexual Harassment in Online Games - Gusnita, chazizah; Nurhadiyanto, Lucky; Ladiqi, Suyatno (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2023)
The purpose of this study is to discuss patterns of child sexual abuse that occur in the online games Minecraft and Hago. The crime of child sexual abuse with the